Transcranial magnetic stimulation in developmental stuttering: Relations with previous neurophysiological research and future perspectives. Issue 6 (June 2017) - Busan, P.; Battaglini, P.P.; Sommer, M.
Highlights: TMS is widely used in motor disorders but its potential is underestimated in developmental stuttering (DS). TMS data suggest that DS is a symptom of a subtle and complex motor dysfunction. TMS sheds light on motor and white matter dysfunctions in DS, highlighted by other techniques. Abstract: Developmental stuttering (DS) is a disruption of the rhythm of speech, and affected people may be unable to execute fluent voluntary speech. There are still questions about the exact causes of DS. Evidence suggests there are differences in the structure and functioning of motor systems used for preparing, executing, and controlling motor acts, especially when they are speech related. Much research has been obtained using neuroimaging methods, ranging from functional magnetic resonance to diffusion tensor imaging and electroencephalography/magnetoencephalography. Studies using transcranial magnetic stimulation (TMS) in DS have been uncommon until recently. This is surprising considering the relationship between the functionality of the motor system and DS, and the wide use of TMS in motor-related disturbances such as Parkinson's Disease, Tourette's Syndrome, and dystonia. Consequently, TMS could shed further light on motor aspects of DS. The present work aims to investigate the use of TMS for understanding DS neural mechanisms by reviewing TMS papers in the DS field. Until now, TMS has contributed to the understanding of the excitatory/inhibitory ratio of DS motor functioning, also helping to better understand and critically review evidence about stuttering mechanisms obtained from different techniques, which allowed the investigation of cortico-basal-thalamo-cortical and white matter/connection dysfunctions.